2018
DOI: 10.12740/app/84886
|View full text |Cite
|
Sign up to set email alerts
|

Arnold-Chiari malformation and agenesis of the corpus callosum in a case of brief psychotic disorder

Abstract: We report a case of a brief psychotic disorder with type I Arnold-Chiari malformation and agenesis of the corpus callosum which was detected on a magnetic resonance imaging (MRI) scan. The patient was started on antipsychotics and underwent decompression surgery. He is on regular follow-up and returned to normal daily life within a few weeks. The antipsychotics were tapered and eventually stopped, and the patient is maintaining well in the follow-up. With improved neuroimaging techniques reporting brain morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In achieving the second and fourth aims of our study, we found that PLEs may occur in the general population not only in the form of attenuated psychotic symptoms, but also as an expression of individual differences with no clinical threat to mental health or even as a side effect of neurological disorders (Bondade, Kumar, & Hussain, 2018; Chrobak et al, 2016). Low cut‐off points for the general population may prevent the differentiation of UHR individuals from healthy individuals who score high in trait psychoticism or schizotypy.…”
Section: Discussionmentioning
confidence: 82%
“…In achieving the second and fourth aims of our study, we found that PLEs may occur in the general population not only in the form of attenuated psychotic symptoms, but also as an expression of individual differences with no clinical threat to mental health or even as a side effect of neurological disorders (Bondade, Kumar, & Hussain, 2018; Chrobak et al, 2016). Low cut‐off points for the general population may prevent the differentiation of UHR individuals from healthy individuals who score high in trait psychoticism or schizotypy.…”
Section: Discussionmentioning
confidence: 82%
“…Several factors can explain the symptoms of schizophrenia in patients with agenesis of the corpus callosum 8,9 . The corpus callosum has intimate connections with other limbic structures such as the hippocampus and cingulate cortex during embryonic development, and there is ample evidence that these structures are involved in patients with schizophrenia 1,10 . Additionally, aberrant neuronal connections between the two cerebral hemispheres, which might be the cause of many neurological symptoms such as seizures, have been considered as one of the underlying mechanisms of the biological causes of schizophrenia 7,10 .…”
Section: Discussionmentioning
confidence: 99%
“…The Corpus callosum is the largest white matter structure of the human brain involved in interhemispheric signal transmission 1 . The incidence of corpus callosum agenesis is about 1:4000 among live births, which can be either complete or partial and can occur as an isolated anomaly or a part of other syndromic disorders 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…A congenital corpus callosum disorder (CCD) is characterized by a completely or partially absent or misshapen corpus callosum, causing a heterogeneous array of cognitive, psychological, psychiatric, and physical impacts ranging from mild to severe Edwards et al, 2014;Margari et al, 2016;Siffredi et al, 2018). One or more associated neurological developmental and psychiatric disorders including epilepsy, autism, intellectual disability, attentiondeficit/hyperactivity disorder (ADHD), depression, anxiety, and schizophrenia are often present in individuals with a CCD (Bondade et al, 2018;Chinnasamy et al, 2006;Moes et al, 2009;Moreau et al, 2021;Popoola et al, 2019;Simon et al, 2008;Valenti et al, 2019).…”
mentioning
confidence: 99%
“…However, CCDs in adults may be undiagnosed, with neurodevelopmental challenges attributed to associated diagnoses or even personal shortcomings (Maxfield et al, 2021;Paul et al, 2007). There are examples of undiagnosed adults presenting with incidental injuries or psychological/psychiatric symptoms warranting neuroimaging, which subsequently reveal a CCD (Bondade et al, 2018;Chinnasamy et al, 2006;Moreau et al, 2021;Popoola et al, 2019;Simon et al, 2008;Valenti et al, 2019). CCDs remain poorly understood within the health, social care, and education systems, and in the wider community (Edwards et al, 2014).…”
mentioning
confidence: 99%